Individual Needs Terhadap Subjective Well-Being - Nur Hendra Sucipto; Abdul Rahman Saleh (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
This study aims to examine the effect of individual needs on subjective well-being employees in the PPKGBK office (Center for Management of the Bung Karno Complex). This research uses a quantitative approach involving 161 PPKGB employees. Sampling was carried out using probability sampling with accidental sampling technique. The author uses a measuring instrument namely The Modified BBC Subjective Well-Being Scale (BBC-SWB) developed by Kinderman, Schwannauer, Pontin & Tai (2011). The data analysis technique used to answer the research question is multiple regression analysis. Based on the results of the major hypothesis test, the first conclusion obtained from this study is that there is a significant influence between individual needs on subjective well-being of employees at the headquarters of the Bung Karno complex management. Then, based on the results of the minor hypothesis test there are two variables whose regression coefficient values are significant namely: abasement dan achievement, while 14 other variables were not significant.